2019
DOI: 10.1021/acs.jpcc.9b04522
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Metal Oxide/Polymer Molecular Hybrid Interfaces with Nanoscale Resolution Using AFM-IR

Abstract: Obtaining chemical information from the buried interface of an organic coating is not straightforward. In this paper, for the first time, atomic force microscopybased infrared spectroscopy (AFM-IR) is used to probe the chemical interactions at the metal oxide/polymer interface. AFM-IR is a novel technique that provides chemical spectra with spatial resolution below the optical diffraction limits. Poly(acrylic acid) (PAA) on aluminum oxide was chosen as a model system. Two different approaches were used: a thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The carboxylate may have been derived from a corrosion inhibitor of the copper wire 54,55 or a reaction of the copper ions diffused from the wire with acrylic acid and/or other carboxylic acid, which may originate from unreacted 56 and/or degraded epoxyacrylate. 9,57 It has been reported that acrylic acid reacts with not only aluminum 2,29,58 and iron 59 but also copper 60 to generate carboxylate. Because the measured interface is approximately 40 µm away from the edge of the copper wire (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The carboxylate may have been derived from a corrosion inhibitor of the copper wire 54,55 or a reaction of the copper ions diffused from the wire with acrylic acid and/or other carboxylic acid, which may originate from unreacted 56 and/or degraded epoxyacrylate. 9,57 It has been reported that acrylic acid reacts with not only aluminum 2,29,58 and iron 59 but also copper 60 to generate carboxylate. Because the measured interface is approximately 40 µm away from the edge of the copper wire (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, atomic force microscopy-based nanoscale infrared spectroscopy (AFM-IR), for which the highest spatial resolution of 10 nm can be achieved, was developed by Dazzi et al. 21–24 and has been applied to various types of systems 2147 including polymer-metal interfaces. 26–31 The AFM-IR utilizes a sharp AFM probe with a typical tip radius of several tens of nanometers to detect local photothermal expansion of a sample surface induced by absorption of infrared (IR) irradiation, and its spatial resolution depends on the thermal expansion area detected by the apex of an AFM probe tip.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations